Mechanical properties of polypropylene composites based on natural fibers subjected to multiple extrusion cycles - Moran, Juan Ignacio (2007)
The influence of multiple extrusion cycles on the behavior of natural fibers-reinforced polypropylene was studied. Composites were fabricated with 20 wt % of flax fibers. Final fibers dimensions (length and diameter) were measured by means of optical microscopy. Mechanical properties of matrix and composites were measured after each extrusion cycle. It was observed that the elastic modulus increased by fibers incorporation. The elastic modulus of the matrix was higher after the first process cycle than that of the virgin material, mainly because of chain scission. In the next cycles, the modulus kept constant. On the other hand the elastic modulus of the com posite after a single extrusion step was lower than that predicted by the Halpin-Tsai model probably because of a poor mixing and to low adhesion at the fiber-matrix interface. In the following two steps, modulus increased because the better fiber dispersion was observed. For the final two extrusion cycles, the slow decrease in this property was correlated with the darkening and poor organoleptic properties observed as a result of thermal degradation.